FAKTOR MENINGKATNYA EKSPOR BUAH PALA INDONESIA-UNI EROPA - Dewi, Nila Sukma; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research analyzes the factors of increase of Indonesia nutmeg export to European Union. The Export obstructed by quality standards of nutmeg in 2010-2011, whiches Indonesia received 21 notification from Indonesian Rapid Alert System for Food and Feed (INRASFF), based on notification from European Rapid Alert System for Food and Feed (EU -RASFF). In case, the export obstructed causd by detection of nutmeg containing aflatoxin or fungus that are concern for health. This research applying descriptive qualitative methods and library research. The author used international cooperation theori by K.J. Holsti with the level of the nation-state analysis with liberalism perspective. The sources of this research are from of journals, books, publications, articles and internet.This study focused on Indonesian government efforts to increase exports of nutmeg to global market, especially to the EU market. The effort is Trade Support Programme II (TSP II) cooperate with European Union in October 2011 util October 2015. The purpose of TSP II cooperation for aid repair coordination and transparency of trade policies related to increased exports and repair quality suitability export products, including agricultural products such as nutmeg. The results of this study is, increasing exsport indonesia proved the value of EU imports in 2013 worth US $ 32.15 million, and in April 2015 increased by 20.7% to US$ 86,096 million. In summary, TSP II cooperation can increase exsport of nutmeg Indonesia-EU.Keywords : Exports, Import, Nutmeg, TSP II, INRASFF, EU-RASFF